Seasonally gross alpha and beta activity concentration in bottom and mid-depth water in Sir Dam Pond (Kahramanmaras, Turkey) - Cam, H.; Kucukonder, A.; Durdu, B. G.; Dogru, M.; Karatepe, S. (Carl Hanser Verlag, 2019)
Seasonally grass alpha - beta aclivilies were measured in Bottom and in Mid-depth water in Sir Danz Pond (Kahramanmaras, Turkey). Six sampling sites were pre-defined in different locations of the Sir Dam Pond. The samples collected in spring in May, in the autumn in October. The values of measured gross alpha and gross beta are compared with recommended activity concentration of WHO (Word Health Organization). Obtained results are in good agreement with the values recommended by WHO.
Keywords: Radioactivity; Surface